Analysis of competing risks model using the generalized progressive hybrid censored data from the generalized Lomax distribution - Amal Hassan; Sudhansu Maiti; Rana Mousa; Najwan Alsadat; Mahmoued Abu-Moussa (AIMS Mathematics)
The competing risk (CR) model is crucial for studying various areas, such as biology, econometrics, and engineering. When multiple factors could cause a product to fail, these factors often work against each other, resulting in the product's failure. This scenario is known as the CR problem. This study focused on parameter estimation of the generalized Lomax distribution under a generalized progressive hybrid censoring scheme in the presence of CR when the cause of failure for each item was known and independent. Both maximum likelihood (ML) and Bayesian approaches were used to estimate the unknown parameters, reliability characteristics, and relative risks due to two causes. Bayesian estimators under gamma priors with different loss functions were generated using Markov chain Monte Carlo, and confidence intervals (CIs) were generated using the ML estimation method. Additionally, two bootstrap CIs for the unknown parameters were presented. According to the conditional posterior distribution, credible intervals and the highest posterior density intervals were further generated. The performance of different estimators was compared using Monte Carlo simulation, and real-data applications were used to verify the proposed estimates.